KONTRIBUSI KESEGARAN JASMANI TERHADAP HASIL BELAJAR PENJASORKES SISWA PUTRA SDN 9 BENGKALIS KECAMATAN BENGKALIS - Hafiszullah Hafiszullah; Saripin Saripin; Kristi Agust (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
ABSTRACT This study aims to look at the contribution of physical fitness on learning outcomes. The variables in this study are physical fitness as the independent variable (x) and learning outcomes as the dependent variable (y). This type of research is correlational. While a study is in SDN 9 Bengkalis District of Bengkalis. Population in this research is class IV and V as many as 55 people. Sampling using purposive sampling technique by setting the boys as the study sample as many as 34 people, data analysis in this study uses product moment correlation and linear regression coefficient determined her and further determination. Based on the calculation results of the analysis showed that physical fitness son (X), have a significant relationship and make a meaningful contribution to the learning outcomes (Y), P = 0.042> 0.05α. On the correlation table analysis, research data can be read that the relationship (correlation) with the physical fitness of learning outcomes worth 0350> r-tab 0339, meaning a strong relationship of physical fitness. Based on the strength of the relationship to the two variables, then the value of the regression equation can be described as follows: Y = 6242 + 0088 X, with Fhit 4472> Ftab 4.17 and Thit 2115> Ttab1.697. Thus the proposed working hypothesis (Ha) is acceptable. Furthermore, determination values obtained data analysis (r2) of 0.123. It means that physical fitness can only contribute 12.3% to the learning outcomes.Keywords : Physical Fitness, Learning Outcomes